Repeated Sexual Assault and HIV Seropositivity: A Case Report - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Sexual assaults are on an epidemic level in the Transkei region of South Africa, despite the government efforts to bring it down. Human Immuno-deficiency Virus (HIV) is also proportionally high in this region of South Africa. Objective: To highlight the problem of sexual assault and HIV infection in the Transkei region of South Africa. Case history: This is a case report of 15-year-old teenagers (SD) who was a schoolgirl in standard 6 when she was assaulted. SD was sexually assaulted repeatedly by an older man of 28 years. She was found sero-converted on HIV testing. On physical examination the introitus was red and bruised. A copious amount semen-like infected fluid was observed in her vagina. The case history, findings, beliefs, and compliance with HIV drugs are discussed. Conclusion: There is high risk of repeated sexual assault and HIV infection in the Transkei region of South Africa. Government must look deeper to prevent these rape attacks as well as HIV infection